Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1007/bf01807652
|View full text |Cite
|
Sign up to set email alerts
|

Androgen metabolism and apocrine differentiation in human breast cancer

Abstract: Metabolism of (7 alpha-3H)testosterone has been measured in 111 human breast cancers and compared retrospectively with the degree of apocrine differentiation in the tumors. Cancers in which apocrine characteristics were a marked feature metabolized significantly more testosterone precursor than those in which apocrine features did not predominate. Higher metabolism was accounted for by increased conversion to 5 alpha-reduced products such as 5 alpha-dihydrotestosterone and 5 alpha-androstanediols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…For example, SRD5A1, the 5a-reductase which converts testosterone to dihydrotestosterone, is overexpressed in the apocrine and basal groups (Figure 1c panel 3). This is consistent with previous data showing increased 5a-reductase biochemical activity in apocrine tumours (Miller et al, 1985). The GO analysis revealed the presence of many genes involved in steroid metabolism in the apocrine group.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…For example, SRD5A1, the 5a-reductase which converts testosterone to dihydrotestosterone, is overexpressed in the apocrine and basal groups (Figure 1c panel 3). This is consistent with previous data showing increased 5a-reductase biochemical activity in apocrine tumours (Miller et al, 1985). The GO analysis revealed the presence of many genes involved in steroid metabolism in the apocrine group.…”
Section: Discussionsupporting
confidence: 92%
“…Although apocrine carcinoma is rare, tumour cells with apocrine features have been reported in up to 63% of cases (Miller et al, 1985). The poor survival of the patients with the molecular apocrine profile in the Sorlie and van't Veer studies (Figure 5b) is consistent with the poor prognosis expected for ER-negative, ERBB2-positive tumours.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Origin of apocrine tumours: relationship between benign apocrine metaplasia and apocrine carcinomas Apocrine differentiation of breast epithelial cells has attracted a great deal of attention as up to 50% of breast invasive carcinomas exhibit areas with apocrine morphology features [22][23][24][25][26][27][28], and because available data have shown that women with breast apocrine cystic disease have an increased propensity for developing breast cancer later in their lives [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%